2019
DOI: 10.3389/fmicb.2019.00702
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of Marine Bacterial Polyunsaturated Fatty Acid and Long-Chain Hydrocarbon Biosynthesis

Abstract: Various marine gamma-proteobacteria produce omega-3 polyunsaturated fatty acids, such as eicosapentaenoic acid (20:5, EPA) and docosahexaenoic acid (22:6, DHA), which are incorporated into membrane phospholipids. Five genes, designated pfaABCDE , encode the polyketide/fatty acid synthase necessary for production of these long-chain fatty acids. In addition to de novo biosynthesis of EPA and DHA, the “Pfa synthase” is also involved with production of a long-chain po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The levels of DHA were influenced by lactation time as well ( Table 6 ), and by dietary factors as nuts ( r = 0.284, p = 0.014) and cereal ( r = 0.318, p = 0.006) intake, but no association between Proteobacteria and these dietary factors was detected. Thus, Proteobacteria could be other factor that influences the levels of DHA in breast milk, as it has been demonstrated that some groups of Proteobacteria can synthetize omega-3 polyunsaturated fatty acids such as EPA (eicosapentaenoic) and DHA [ 70 , 71 ]. The genus Staphylococcus was positively correlated with C18:2 (n-6) 9,12 t ( r = 0.309, p = 0.035) and C18:2 (n-6) 10 t , 12 ( r = 0.301, p = 0.040) isomers [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…The levels of DHA were influenced by lactation time as well ( Table 6 ), and by dietary factors as nuts ( r = 0.284, p = 0.014) and cereal ( r = 0.318, p = 0.006) intake, but no association between Proteobacteria and these dietary factors was detected. Thus, Proteobacteria could be other factor that influences the levels of DHA in breast milk, as it has been demonstrated that some groups of Proteobacteria can synthetize omega-3 polyunsaturated fatty acids such as EPA (eicosapentaenoic) and DHA [ 70 , 71 ]. The genus Staphylococcus was positively correlated with C18:2 (n-6) 9,12 t ( r = 0.309, p = 0.035) and C18:2 (n-6) 10 t , 12 ( r = 0.301, p = 0.040) isomers [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our findings suggest microbes might also use β-lactones as intermediates since we detected a number of β-lactone synthetase hits in gene clusters known to make natural products without final βlactone moieties such as polyunsaturated fatty acids. Indeed, β-lactone synthetases in oleABCD gene clusters were recently linked to production of the final alkene moiety in the biosynthesis of a C31 polyunsaturated hydrocarbon product (43). Such cases, if more widespread, may have also escaped detection because most of the predicted gene clusters with β-lactone synthetases were not detected by tools like antiSMASH until recently (23), prohibiting the discovery of such biosynthetic pathways through genome mining approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest microbes might also use β-lactones as intermediates since we detected a number of β-lactone synthetase hits in gene clusters known to make natural products without final βlactone moieties such as polyunsaturated fatty acids. Indeed, β-lactone synthetases in oleABCD gene clusters were recently linked to production of the final alkene moiety in the biosynthesis of a C31 polyunsaturated hydrocarbon product (40). Such cases, if more widespread, may have also escaped detection because most of the predicted gene clusters with β-lactone synthetases were not detected by tools like antiSMASH (20) until recently, prohibiting the discovery of such biosynthetic pathways through genome mining approaches.…”
Section: Discussionmentioning
confidence: 99%